DRYING TIME ESTIMATION OF CARRAGEENAN-EGG WHITE MIXTURE AT TRAY DRYER - Mohamad Djaeni; Aji Prasetyaningrum; Nurul Asiah; Ratnawati Hartono (International Journal of Science and Engineering, 2014)
The drying is the last step to find carrageenan product. Currently, the carrageenan drying still deals with too long drying time. This because, during the process carrageenan and water forms gel stucture in which hampers the water diffusion to the surface. Foaming agent introduction such as egg white can be considered to break the gel structure and make the drying process being smooth and fast. This paper discusses the effect of egg white as foaming agent on the drying time of carrageenan. In this study, the carrageenan was mixed with egg white to form foam that can break the gel and create the pore for improving the surface area.  The carrageenan and egg white mixture was then dried at different air temperature and humidity. Results showed that the drying time was shortened with the presence of egg whiet as well as the increase of air temperature. For example, the drying time at air temperature 80oC with  20 % egg white was about 60 minutes shorter than that of without foam. In addition, the lowering air dehumidification affected the drying time positively.